Coconut Candy Cutter Machine for Small Medium Enterprise (SMEs) Businesses - Mohd Razali, Nik Muhammad Syazwan; Ab Rahman, Azmanirah; Subramaniam, Tamil Selvan; Ahmad Azrai, Munirah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: The coconut candy cutting machine is a product developed to simplify the cutting process and improve the hygienic quality of coconut candy. This research used the design model of Design Thinking, which consists of the phases of empathy, definition, ideas, prototype, and testing. The objective of this study was to design, develop and test the functionality of a coconut candy cutting machine operated by the Blynk application. The project used components such as linear drive motors, relays and the NodeMCU ESP8266 microprocessor. Based on evaluation from experts, found that they agree with The Prototype of Coconut Candy Cutter Machine for Small Medium Enterprise (SMEs) Industry in terms of design, function, and suitability. Besides, the coconut candy cutting machine makes coconut cut with the correct size before being distributed to consumers. Keywords: Coconut candy cutter machine, Blynk application, Design Thinking